Directional preference of European lobster (Homarus gammarus) movements on the Yorkshire Coast - James Michael Wood (Journal of Fisheries, 2016)
Recaptures of 838 tagged Homarus gammarus individuals identified a directional preference, with bearings from release to recapture concentrated along a North-West to South-East axis, aligning with the predominant current direction for the study site.